Microwave Assisted Synthesis, Spectroscopy Characterization of Amoxicillin Linked Azomethine as Medical Applications (Open Herald: Periodical of Methodical Research, 2025)
In this study, a new amoxicillin linked azomethine synthesis (A1-A3) by reacting amoxicillin with different aldehydes such as 2-hydroxy5-hexylBenzaldehyde, 4- Hexoxybenzaldehyde, and 2-methoxybenzaldehyde. FT-IR characterized the derivatives (A1-A3). All the derivatives (A1-A3) were evaluated against microorganisms such as Streptococcus pneumonia and E. coli by zone inhibition method. The findings demonstrated that certain derivatives exhibit superior antibacterial properties in comparison to the efficacy of the original drug. The produced azomethine derivative A1 has the most promising antimicrobial properties against Staphylococcus aureus by zone inhibition 23 mm at higher dosages. However, derivative A2 reduced efficacy at lower dosages requires more investigation to improve potency and stability. Evaluation of prostate cancer (PC3) by using MTT assay that gives a positive result at high concentration.